1995
DOI: 10.1093/infdis/172.5.1312
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Prophylaxis of Experimental Staphylococcal Endophthalmitis: Comparative Efficacy of Sparfloxacin, Peftoxacin, Imipenem, Vancomycin, and Amikacin

Abstract: The preventive efficacy of several antibiotics in experimental staphylococcal endophthalmitis was evaluated. Two hours before bilateral intravitreal infection with 500 cfu of Staphylococcus aureus, 18 pigmented phakic rabbits were assigned to receive a single intramuscular injection of sparfloxacin (50 mg/kg), pefloxacin (50 mg/kg), imipenem (50 mg/kg), vancomycin (30 mg/kg), amikacin (15 mg/kg), or saline and were killed 24 h after infection (6 eyes/group). Sparfloxacin, pefloxacin, and imipenem were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…However, experimental data suggest that intravitreal corticosteroids may be beneficial. Quinolone antimicrobials have been increasingly studied in endophthalmitis [12][13][14][15][16]. The quinolones as a group remain potentially beneficial because they provide the advantage of a broad spectrum, excellent penetration into biologic fluids including the aqueous and vitreous humor, and rapid bactericidal action [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, experimental data suggest that intravitreal corticosteroids may be beneficial. Quinolone antimicrobials have been increasingly studied in endophthalmitis [12][13][14][15][16]. The quinolones as a group remain potentially beneficial because they provide the advantage of a broad spectrum, excellent penetration into biologic fluids including the aqueous and vitreous humor, and rapid bactericidal action [28].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, quinolone antimicrobials have been tried for both the prophylactic [12] and curative [15,16] treatment of infectious endophthalmitis. MarrakchiBenjaafar et al [12] used various antibiotics in the systemic prophylaxis of experimental staphylococcal endophthalmitis and reported that the systemic administration of sparfloxacin can prevent the development of experimental endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Staphylococcus epidermidis is the most common cause of postoperative endophthalmitis [1,2]. Systemic, topical, subconjunctival and intravitreal forms of administration of various antibiotics, including cefazolin [3], vancomycin [4,5] and quinolones [6,7], have been tried for the treatment of bacterial endophthalmitis caused by S. epidermidis with limited success. Trovafloxacin is a novel fluoroquinolone effective against gram-positive organisms compared with currently available antimicrobial agents of this class including ciprofloxacin and ofloxacin [8].…”
mentioning
confidence: 99%